Bahasa indonesia PENGARUH PENDIDIKAN DAN STATUS PEKERJAAN IBU DENGAN PEMBERIAN MP-ASI BAYI 6-12 BULAN DI WILAYAH KERJA PUSKESMAS SUKO BINANGUN - Liliana, Anita; Desmawati, Betri (Coping: Community of Publishing in Nursing; Vol 10 No 4 (2022): Agustus 2022DO - 10.24843/coping.2022.v10.i04.p10, 2022)
The allocation of weaning food (MP-ASI) needed to be given appropriately. Allocating weaning food too early could disrupt the exclusive breastfeeding, and it could increase infant mortality. Besides, the allocation of weaning food (MP-ASI) or improper food control could cause malnutrition. The education and occupation of mother were one of the factors that affected the allocation of weaning food. This study aims to indicate the effects of education level and occupation status of mother with the allocation of weaning food for baby in the age around 6-12 months in Sri Busono village, the working area of Suko Binangun Public Health Center, Way Seputih, Lampung Tengah District. This study used quantitative method with analytic study and cross sectional survey design. It used total sampling technique with 30 respondents. Therefore, the instrument of this study was questionnaire. The bivariate analysis used chi square and kolmogorov smirnov. The result showed that most of mothers with basic education (elementary school / junior high school) were 46,7%. The unemployed mothers were 73,3%. The unfulfilled allocation of weaning food was 60,00%. The test results showed that p = 0,000, it can be concluded that there were the effects of education level and occupational status of mother with the allocation of weaning food.